Wim Delvoye’s astonishing art shows what’s lurking in the banal - Messham-Muir, Kit (The Conversation Media Group, 2014)
When Belgian artist Wim Delvoye broke onto the international scene back in the 1990s, he was one of those artists (like Sigmar Polke before him) that critics found difficult to pigeonhole. His works ranged from the ornate to the scatological, and were often both. Two decades on, and now in his late-40s, his work is often placed within the tensions of the “sacred” and the “profane”.